Temporal variation in the soil properties and rice yield of organic rice farming in the tropical monsoon region, Indonesia - Syamsiyah, Jauhari; Ariyanto, Dwi Priyo; Komariah, Komariah; Herawati, Aktavia; Dwisetio, Pertiwi Kurnia; Sari, Safira Indrias; Salsabila, Harjayanti Auliyaa; Herdiansyah, Ganjar; Hartati, Sri; Mujiyo, Mujiyo (Universitas Sebelas Maret, 2023)
One of the organic farming goals is improving soil properties to support sustainable rice production. This study investigated the soil properties and rice yields under temporal variation of organic rice fields. Soil sampling was conducted in organic rice fields with three temporal variations, namely 0, 4, 7, and 10 years in a tropical monsoon region in Central Java, Indonesia. Variables observed included soil organic carbon, soil carbon stock, soil microbes population, dissolved organic carbon, soil liquid limit, soil sticky limit, soil plasticity limit, soil color changing limit, soil friability, soil porosity, soil total nitrogen, soil total phosphorus, soil available sulfur, exchangeable calcium, cation exchange capacity, total potassium, bulk density, base saturation, exchangeable sodium, exchangeable potassium, and rice yield. This study confirms that soil organic carbon increased by 51.63% within 10 years (from 1.84% to 2.79%). Organic farming also improved all the physical, chemical, and biological soil properties, by the increase of soil organic carbon. However, soil organic carbon is mostly determined by soil cation exchange capacity, soil total phosphorus, and soil porosity. The mechanism of rice yield increase in organic rice farming is not affected by soil organic carbon directly but through the synergic increase in soil total nitrogen. The 1% increase of soil organic carbon increases 0.065% of soil total nitrogen hence rice yield increases by 1.66 tons ha-1. This study supports sustainable agriculture by providing evidence of improved soil properties under organic farming.